Beejal is solving the equation y/7 − 3 = 39


As a first step, he starts by adding ? to both sides of the equation, and then continues by multiplying by on each side

1 answer

To solve the equation \( \frac{y}{7} - 3 = 39 \), let's follow Beejal's first step.

  1. Add 3 to both sides of the equation:

    \[ \frac{y}{7} - 3 + 3 = 39 + 3 \]

    This simplifies to:

    \[ \frac{y}{7} = 42 \]

  2. Now, to eliminate the fraction, multiply both sides by 7:

    \[ 7 \cdot \frac{y}{7} = 42 \cdot 7 \]

    This simplifies to:

    \[ y = 294 \]

So the answer to Beejal's first step is to add 3, and then he multiplies by 7. The final solution to the equation is \( y = 294 \).